2006
DOI: 10.1007/s10585-006-9040-z
|View full text |Cite
|
Sign up to set email alerts
|

Tiam1 regulates cell adhesion, migration and apoptosis in colon tumor cells

Abstract: The guanine nucleotide exchange factor Tiam1 regulates numerous biologic properties including migration and invasion. We demonstrated previously that colon tumor cells biologically selected for increased migration were increased in Tiam1 expression. Cells selected for increased Tiam1 expression or that ectopically overexpress Tiam1 were increased in metastatic potential. Here, we demonstrate that Tiam1 regulates additional functions associated with metastasis, including reduced cellular adhesion and resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
77
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 44 publications
4
77
1
Order By: Relevance
“…T cell lymphoma invasion and metastasis 1 (Tiam1) serves as a specific GEF for Rho GTPase Rac1 (16). Although it has been well established that Tiam1 plays important roles in tumor progression and metastasis (17)(18)(19)(20), the specific mechanisms regulating its activity and protein stability are far from clear (21,22). It has been reported that Src-induced adherens junction disassembly and cell migration involve phosphorylation and degradation of Tiam1, likely through calpain proteases (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T cell lymphoma invasion and metastasis 1 (Tiam1) serves as a specific GEF for Rho GTPase Rac1 (16). Although it has been well established that Tiam1 plays important roles in tumor progression and metastasis (17)(18)(19)(20), the specific mechanisms regulating its activity and protein stability are far from clear (21,22). It has been reported that Src-induced adherens junction disassembly and cell migration involve phosphorylation and degradation of Tiam1, likely through calpain proteases (20).…”
mentioning
confidence: 99%
“…Moreover, Tiam1 negatively regulated anoikisinduced apoptosis in a Rac1-independent manner, suggesting that other effectors are probably involved in this form of cell death (18). It has also been reported that Tiam1 is required for * This work was supported by National Natural Science Foundation of China Grants 31221064 and 81272235 (to W. W) .…”
mentioning
confidence: 99%
“…Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion and progression (13). Moreover, numerous studies have demonstrated that the upregulation of Tiam1 is associated with an aggressive phenotype and a poor clinical outcome in several types of malignant tumors, including breast (14), colon (15), prostate (16), liver (17) and nasopharyngeal (11) esophageal squamous cell carcinoma (18). However, to date, the correlation between Tiam1 expression and ovarian carcinoma has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of TIAM1 has been reported in various solid tumors (5)(6)(7)(8)(9)(10)(11)(12). In addition, previous studies have demonstrated that TIAM1 modulates a number of cellular processes considered to be associated with tumor progression, including cell apoptosis, invasion and migration (13)(14)(15)(16)(17)(18) To gain insight into the potential role of miR-10a, miR-22, miR-340, miR-342-3p, miR-590-5p and TIAM1 in the pathogenesis of ENKTCL, the present study examined the expression levels of these miRNAs and their target gene TIAM1 in ENKTCL tissues, in order to assess whether the expression levels of these molecules correlated with the clinical features of patients with ENKTCL.…”
Section: Introductionmentioning
confidence: 99%